2018
DOI: 10.1063/1.5017278
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Hofmeister series beyond water: Specific-ion effects in non-aqueous solvents

Abstract: We present an experimental investigation of specific-ion effects in non-aqueous solvents, with the aim of elucidating the role of the solvent in perturbing the fundamental ion-specific trend. The focus is on the anions: CHCOO>F>Cl>Br>I>ClO>SCN in the solvents water, methanol, formamide, dimethyl sulfoxide (DMSO), and propylene carbonate (PC). Two types of experiments are presented. The first experiment employs the technique of size exclusion chromatography to evaluate the elution times of electrolytes in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
78
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(80 citation statements)
references
References 48 publications
2
78
0
Order By: Relevance
“…With regard to this point, some ion pairs are more stable than others which also depends on the chosen solvent and further components of the solution. Corresponding experimental and simulational approaches suggested that this behavior is universal and occurs for all ions in aprotic as well as protic solvents due to different solvation interactions [18,20,34,74,[90][91][92]. Previous explanations for these effects often cite the law of matching water affinities (LMWA), which states that ion pairs with comparable water affinities reveal the highest ion pair formation stabilities [93].…”
Section: Specific Ion Effectsmentioning
confidence: 99%
“…With regard to this point, some ion pairs are more stable than others which also depends on the chosen solvent and further components of the solution. Corresponding experimental and simulational approaches suggested that this behavior is universal and occurs for all ions in aprotic as well as protic solvents due to different solvation interactions [18,20,34,74,[90][91][92]. Previous explanations for these effects often cite the law of matching water affinities (LMWA), which states that ion pairs with comparable water affinities reveal the highest ion pair formation stabilities [93].…”
Section: Specific Ion Effectsmentioning
confidence: 99%
“…In contrast to simple electrostatic mean-field approaches, recent numerical and experimental findings indeed revealed the occurrence of various ion complex states. Hence, ions and solvent molecules aggregate within the Bjerrum length to ion-solvent complexes with distinct stoichiometries, as influenced by the ion species, the ion concentration, and the molecular properties of the solvent molecules [45,53,63,[67][68][69][70][71][72][73][74][75][76][77][78].…”
Section: Distinct States Of Ion Complexesmentioning
confidence: 99%
“…For some solvents and specifically for water, differences in the complex formation tendencies for distinct ions are observed, which can be rationalized by the influence of specific ion effects [38,54,63,68,70,75,[83][84][85][86]. These effects are often observed in aqueous solutions, whereas studies of specific ion effects in organic solvents are rather sparse [30,[76][77][78]87]. A series of seminal studies [35][36][37] regarding the solubility of various lithium salts in acetonitrile reveals the following order, LiPF 6 < LiFSI < LiTFSI ≤ LiClO 4 < LiBF 4 LiCF 3 CO 2 , which coincides with the observed tendency of ion complex formation.…”
Section: Specific Ion Effectsmentioning
confidence: 99%
See 2 more Smart Citations